2017
DOI: 10.1007/s00381-017-3660-2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided placement of ventricular catheters in first-time pediatric VP shunt surgery

Abstract: Ultrasound-guided VC placement is as precise as frameless navigated placement. The optimal VC position was associated to a significant lower VC obstruction rate. The frontal position was superior to the occipital. Intraoperative US guidance is fast with almost no extra time and no extra cost. US-guided VC placement should become standard of care in VP shunt surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…7 In some studies, occipital position of VPS has been inferior to frontal position regarding patency and functioning of the shunt. 8,9 An association between location of the shunt and correct positioning of the proximal catheter was not observed in the two cohorts. 10 Operation time was shorter in the US cohort.…”
Section: Study Results In Context With Current Literaturementioning
confidence: 82%
See 3 more Smart Citations
“…7 In some studies, occipital position of VPS has been inferior to frontal position regarding patency and functioning of the shunt. 8,9 An association between location of the shunt and correct positioning of the proximal catheter was not observed in the two cohorts. 10 Operation time was shorter in the US cohort.…”
Section: Study Results In Context With Current Literaturementioning
confidence: 82%
“…The rate of optimally placed catheters in the US cohort of our study is comparable to the results of other studies analyzing US-GVPS placement. 8 It has been shown in the literature that OC placement lowers the risk for shunt failure, and therefore the need for revision surgery. [14][15][16] This result could be confirmed in our study, since both patients in the US cohort requiring revision surgery showed NOC of their VPS.…”
Section: Study Results In Context With Current Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Initially, the entry point is measured according to standard anatomical landmarks, thereafter the catheter is placed into the ventricle under real-time US guidance along the depicted trajectory (10,11). To date, most of the clinical evidence regarding image-guided VPS placement derives from small retrospective cohort studies (11)(12)(13)(14). To date, studies comparing these two navigation methods in a prospective manner do not exist.…”
Section: Introductionmentioning
confidence: 99%